Creative art therapy program: case study on Malay Muslim inmates at Sungai Udang Prison in Melaka / Azahar Harun...[et.al] - Harun, Azahar; Zakaria, Rosli; Osman, Amirruddin; Ali, Ariff; Ahmad, Hishamudin; Abd Razak, Haslinda; Meor Hamzah, Meor Hasmadi (2016)
This paper presents a case study on Malay Muslim inmates at Sungai Udang Prison in Melaka. By referring to a Triangular Relationship concept founded by art therapists, a new model, which complies with the teaching of Islam, is developed. Basically it encompasses the Client, the Artwork, the Therapist and Allah (the Almighty). From this model two measurement stages (Pre Test and Post Test) were also established. In the PreTest stage, the inmates were instructed to complete four drawing modules that include Contour Drawing (CD), Self Reflection Drawing (SRD), Memory Drawing (MD) and Visual Diary (VD). In the Post Test stage, the inmates were given a task to produce freestyle art on canvas (3' x 4 '). In addition a survey was also conducted to assess the outcome of the program. Based on our observation, it shows that majority of the Malay Muslim inmates were able to demonstrate artistic ability despite limited resources and strict prison rules. Even more interesting is the fact that they were able to visualize inner feelings, emotions and spiritual sense through creative art. We conclude that the creative art therapy program conducted at the Sungai Udang Prison in Melaka has opened a new paradigm for researcher to explore the therapeutic value of creative art in Malaysian prison. The outcome of the study in a way has helped the inmates to divert their negative emotion (angry, anxiety, fear, frustration) and find pleasure in creative art.